Molecular characterization of a heterothallic mating system in Pseudogymnoascus destructans, the Fungus causing white-nose syndrome of bats - Palmer, Jonathan M; Kubatova, Alena; Novakova, Alena; Minnis, Andrew M; Kolarik, Miroslav; Lindner, Daniel L (G3 (Bethesda, Md.), 2014)
White-nose syndrome (WNS) of bats has devastated bat populations in eastern North America since its discovery in 2006. WNS, caused by the fungus Pseudogymnoascus destructans, has spread quickly in North America and has become one of the most severe wildlife epidemics of our time. While P. destructans is spreading rapidly in North America, nothing is known about the sexual capacity of this fungus. To gain insight into the genes involved in sexual reproduction, we characterized the mating-type locus (MAT) of two Pseudogymnoascus spp. that are closely related to P. destructans and homothallic (self-fertile). As with other homothallic Ascomycota, the MAT locus of these two species encodes a conserved α-box protein (MAT1-1-1) as well as two high-mobility group (HMG) box proteins (MAT1-1-3 and MAT1-2-1). Comparisons with the MAT locus of the North American isolate of P. destructans (the ex-type isolate) revealed that this isolate of P. destructans was missing a clear homolog of the conserved HMG box protein (MAT1-2-1). These data prompted the discovery and molecular characterization of a heterothallic mating system in isolates of P. destructans from the Czech Republic. Both mating types of P. destructans were found to coexist within hibernacula, suggesting the presence of mating populations in Europe. Although populations of P. destructans in North America are thought to be clonal and of one mating type, the potential for sexual recombination indicates that continued vigilance is needed regarding introductions of additional isolates of this pathogen.
Keywords: Chiroptera; Ascomycota; white-nose syndrome; Reproduction; mating type; DNA fungální; fungální RNA; geny hub; geomyces; Gene Expression; zvířata; DNA, Fungal; exprese genu; rozmnožování; sexual reproduction; Genes, Fungal; RNA, Fungal; Genetics of Sex; Animals